2022
DOI: 10.3390/fishes7060353
|View full text |Cite
|
Sign up to set email alerts
|

Costimulatory Molecules CD80/86 Trigger Non-Specific Cytotoxic Cell of Nile tilapia (Oreochromis niloticus) to Kill CIK Cells

Abstract: The teleost non-specific cytotoxic cell (NCC), as the evolutionary precursors of NK cells, is an important cytotoxic cell population in the innate immune system of teleost. We have recently realized that costimulatory CD80/86 have conservation in structural and interactional features with its ligand CD28 in Nile tilapia (Oreochromis niloticus). However, the ability of CD80/86 to regulate NCC activity has not been fully investigated. In the present study, we first obtained the recombinant fusion CD80/86 protein… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 35 publications
(42 reference statements)
0
0
0
Order By: Relevance
“…It has been demonstrated that bacillus probiotics like (B. subtilis) can assist in controlling the antioxidant enzyme activity of Nile tilapia. The antioxidant enzymes in fish aid in breaking down potentially harmful chemicals in the water and defend against the damaging effects of free radicals [73,74]. B. subtilis, Bacillus coagulans, and Bacillus cereus boosted SOD activity in Nile tilapia rearing systems.…”
Section: Discussionmentioning
confidence: 99%
“…It has been demonstrated that bacillus probiotics like (B. subtilis) can assist in controlling the antioxidant enzyme activity of Nile tilapia. The antioxidant enzymes in fish aid in breaking down potentially harmful chemicals in the water and defend against the damaging effects of free radicals [73,74]. B. subtilis, Bacillus coagulans, and Bacillus cereus boosted SOD activity in Nile tilapia rearing systems.…”
Section: Discussionmentioning
confidence: 99%